MENGOPTIMALKAN KAMPANYE SOSIAL DIGITAL MELALUI MEDIA ONLINE UNTUK MENINGKATKAN KESADARAN LINGKUNGAN DI KALANGAN MILENIAL DESA TAPULAGA - Sirajudddin; Muh. Rajab; La Ode Herman; Dian Trianita Lestari; La Taya; Harnina Ridwan (JOURNAL OF COMMUNITY DEDICATION, 2025)
This study examines the effectiveness of digital social campaigns through online media in increasing environmental awareness and behavior among millennials. Using a mixed approach (quantitative and qualitative), the study evaluates the relationship between content type, frequency of interaction, and platform selection with audience engagement and understanding of environmental issues. The results indicate that creative and interactive content, such as short videos, infographics, and educational quizzes, can motivate millennials to actively participate in campaigns and adopt environmentally friendly behaviors. Popular social media platforms such as TikTok, Instagram, and WhatsApp have proven effective in reaching and increasing audience engagement, with TikTok ranking highest in terms of engagement. Digital social campaigns not only disseminate information but also foster two-way communication that strengthens the internalization of environmental values ​​and supports sustainable attitudinal change. A structured communication strategy, prioritizing creative content and utilizing modern technology, is key to success in achieving sustainability goals. This study emphasizes the importance of optimal digital campaigns as innovative educational tools to mobilize millennial participation in environmental preservation.